Arc decomposition behavior of C4F7N/Air gas mixture and biosafety evaluation of its by‐products. (4th July 2022) - Ye, Fanchao; Zhang, Xiaoxing; Li, Yi; Wan, Qianqian; Bauchire, Jean‐Marc; Hong, Dunpin; Xiao, Song; Tang, Ju
Abstract: At present, reports on the arc interruption and decomposition behavior of a C4 F7 N/air gas mixture especially the biosafety of its by‐products are limited. Herein, a 57% C4 F7 N/43% air gas mixture was employed as an arc‐quenching medium to conduct 200 breaking tests on a load switch (630 A/24 kV). The arc interruption and decomposition behavior of the gas mixture were evaluated, and the biosafety of the decomposition products was assessed based on an acute inhalation toxicity test. It was found that the average arcing time of the 200 breakings was about 10.1 ms and that breakings were basically completed at the zero‐crossing of the second or third current half‐cycle. The gas mixture after breaking decomposed dramatically (the C4 F7 N content decreased by 75.6%), generating a large number of gaseous by‐products (CO, CF4, C2 F6, C3 F8, CF3 CN, C4 F8, CO2, C4 F10 N2, C3 F6, C2 N2, etc.) as well as solid by‐products (carbon particles). The lethal concentration of 50% (LC50, 4 h) of C4 F7 N/air after 200 breakings was 31 ppm (male mice) and 34 ppm (female mice), respectively, and the toxicity was classified as Grade 1. In general, C4 F7 N has an arc interruption capability, albeit weaker than that of SF6 under the same conditions. After breaking, the C4 F7 N gas mixture has a relatively high acute inhalation toxicity, and relevant safety protection measures for research or operation personnel are strictly needed.